Observation of dark pulses in 10 nm thick YBCO nanostrips presenting hysteretic current voltage characteristics. (16th November 2017) - Ejrnaes, M; Parlato, L; Arpaia, R; Bauch, T; Lombardi, F; Cristiano, R; Tafuri, F; Pepe, G P
Abstract: We have fabricated several 10 nm thick and 65 nm wide YBa2 Cu3 O7− δ (YBCO) nanostrips. The nanostrips with the highest critical current densities are characterized by hysteretic current voltage characteristics (IVCs) with a direct bistable switch from the zero-voltage to the finite voltage state. The presence of hysteretic IVCs allowed the observation of dark pulses due to fluctuations phenomena. The key role of the bistable behavior is its ability to transform a small disturbance (e.g. an intrinsic fluctuation) into a measurable transient signal, i.e. a dark pulse. On the contrary, in devices characterized by lower critical current density values, the IVCs are non-hysteretic and dark pulses have not been observed. To investigate the physical origin of the dark pulses, we have measured the bias current dependence of the dark pulse rate: the observed exponential increase with the bias current is compatible with mechanisms based on thermal activation of magnetic vortices in the nanostrip. We believe that the successful amplification of small fluctuation events into measurable signals in nanostrips of ultrathin YBCO is a milestone for further investigation of YBCO nanostrips for superconducting nanostrip single photon detectors and other quantum detectors for operation at higher temperatures.